DAMPAK PENERAPAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) TERHADAP PENGHIDUPAN PEKERJA SEKTOR INFORMAL DI PROVINSI DKI JAKARTA - Ian Wira Pratama Iskar; Anggih Fajrin Akbar; Willy Dozan; Andis Muhammad Yudiansyah (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2021)
This research aims to explain the large scale social restriction (PSBB) on informal workers in DKI Jakarta province, and to formulate what efforts should be made to mitigate the negative impact of the PSBB. The collection of data in this study uses literary study methods whereby data retrieval is taken from existing media, such as online media and social media. Some of the things that have become the impact of the implementation of social restriction on large scale (PSBB) for informal workers in DKI Jakarta province is the number of workers who are in the paint to reduce the company spending, the buying power in the community is reduced so that the economic Theravada, and for workers who get money from working daily. From the conclusion of the results of this analysis is the government of DKI Jakarta play an important role in the service to the community in fulfilling the life of the community. Key words: Impact evaluation, large-scale social restrictions, Informal sector